(untitled) (Revista Contexto & Educação, 2022)
The experience of the Covid-19 pandemic encourages emergency and structural actions in the context of education. The insertion of information and communication technologies in the educational space introduces yet another tool to mediate the teaching process, modifies the learning architecture and, thus, reconfigures ways of constructing educational activities. In this way, the text on stage constitutes a perception of students about educational technologies in their training. As an investigative strategy, a semi-structured questionnaire was used, which was applied online through google forms and a conversation wheel. 24 students participated in a degree course in Computing at a public university in the city of Manaus. The results emerged from the content analysis, which, as a qualitative analysis technique, highlighted two categories: i) educational technologies in the educational process and ii) the incidence of educational technologies in their training process. Finally, it is noteworthy that the challenges of this situation reverberate the need to reinforce that teacher education is continuous and, in relation to technological innovations, it requires constancy in the face of the numerous changes that forge this field.